Poverty in Mayan children in Quintana Roo, Mexico - Beatriz Gómez (Equidad & Desarrollo, 2023)
Child poverty is a topic that is rarely addressed in the literature on poverty. The reason for this is that its methodology requires field work for anthropometric measurements and observation of the immediate environment. In this sense, the degree of poverty among children of the Yucatecan Mayan ethnic group of Quintana Roo, Mexico, was estimated using an instrument composed of six indicators which was applied in 120 households (271 children) in four Mayan localities in José María Morelos, Quintana Roo. Although signs of poverty were found, the results indicate that it is not as intense as expected.JEL:d31, e24, i32